‘We just look at the well-being of the baby and not the money required’: a qualitative study exploring experiences of quality of maternity care among women in Nairobi’s informal settlements in Kenya - Gilbert Kokwaro; Jackline Oluoch-Aridi; Francis Wafula; Mary B Adam (BMJ Open, 2020)
Objective To examine how women living in an informal settlement in Nairobi perceive the quality of maternity care and how it influences their choice of a delivery health facility.Design Qualitative study.Settings Dandora, an informal settlement, Nairobi City in Kenya.Participants Six focus group discussions with 40 purposively selected women aged 18–49 years at six health facilities.Results Four broad themes were identified: (1) perceived quality of the delivery services, (2) financial access to delivery service, (3) physical amenities at the health facility, and (4) the 2017 health workers’ strike.The four facilitators that influenced women to choose a private health facility were: (1) interpersonal treatment at health facilities, (2) perceived quality of clinical services, (3) financial access to health services at the facility, and (4) the physical amenities at the health facility. The three barriers to choosing a private facility were: (1) poor quality clinical services at low-cost health facilities, (2) shortage of specialist doctors, and (3) referral to public health facilities during emergencies.The facilitators that influenced women to choose a public facility were: (1) physical amenities for dealing with obstetric emergencies and (2) early referral to public maternity during antenatal care services. Barriers to choosing a public facility were: (1) perception of poor quality clinical services, (2) concerns over security for newborns at tertiary health facilities, (3) fear of mistreatment during delivery, (4) use of unsupervised trainee doctors for deliveries, (5) poor quality of physical amenities, and (6) inadequate staffing.Conclusion The study provides insights into decision-making processes for women when choosing a delivery facility by identifying critical attributes that they value and how perceptions of quality influence their choices.